1987
DOI: 10.1002/ffj.2730020205
|View full text |Cite
|
Sign up to set email alerts
|

Application of isobutane and ammonia chemical ionization mass spectrometry for the analysis of volatile terpene alcohols and esters

Abstract: The ionization and fragmentation behaviour of mono-and sesqui-terpene alcohols and esters in CI mass spectrometry was investigated. The reagent gases used were isobutane and ammonia. Isobutane yields the species [MH]' as the quasimolecular ions which, however, are extremely small for many of the investigated compounds.Ammonia gives intense [M + 18]+ quasimolecular adduct ions. The assignment of the molecular mass is more reliable in ammonia than in isobutane CI. Alcohols and esters form characteristic fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Finally, the molecular and quasimolecular ions of the benzofuran euparin (106) were in accord with those obtained in our previous study (Paolini et al, 2005); in effect, these components were characterized by: These results on the chemical ionization of monoterpene esters were in accordance with those previously reported in the study of aerial parts of E. cannabinum subsp. corsicum (Paolini et al, 2005) and with those previously reported in the literature (Bruins, 1979;Hendriks et al, 1985;Lange and Schutze, 1987). The information obtained by GC-CI/MS has been used with respect to unknown esters and diesters for: (i) the determination of molecular mass; (ii) the differentiation of compounds with similar EI/MS; and (iii) the identification of acid and alcohol portions.…”
Section: Gc-ei/ms and Gc-ci/ms Of Unknown Components Not Present In Mmentioning
confidence: 89%
“…Finally, the molecular and quasimolecular ions of the benzofuran euparin (106) were in accord with those obtained in our previous study (Paolini et al, 2005); in effect, these components were characterized by: These results on the chemical ionization of monoterpene esters were in accordance with those previously reported in the study of aerial parts of E. cannabinum subsp. corsicum (Paolini et al, 2005) and with those previously reported in the literature (Bruins, 1979;Hendriks et al, 1985;Lange and Schutze, 1987). The information obtained by GC-CI/MS has been used with respect to unknown esters and diesters for: (i) the determination of molecular mass; (ii) the differentiation of compounds with similar EI/MS; and (iii) the identification of acid and alcohol portions.…”
Section: Gc-ei/ms and Gc-ci/ms Of Unknown Components Not Present In Mmentioning
confidence: 89%
“…Many studies have shown that crustaceans and aquatic animals' growth performance improvements come from various medicinal herbs' extracts (Abdel-Latif et al, 2021;Cheng, 2019;Dong et al, 2018;Pan et al, 2018;Tan et al, 2018). For GBL, it can send out fragrance to stimulate the appetite of crayfish and improve the digestibility and absorption rate of feed in the digestive tract of the crayfish (Lange and Schultze, 2010;Jannathulla and Dayal, 2022). In addition, it is rich in protein.…”
Section: Discussionmentioning
confidence: 99%